Uso de um escore derivado do hemograma na predição de risco de pacientes submetidos à cirurgia cardíaca com circulação extracorpórea - Rödel, Ana Paula Porto (2015)
Some CBC parameters have been implicated in individual susceptibility to death, both in heart disease and cardiac surgery populations. The cellular elements of blood are widely affected during cardiopulmonary bypass (CPB), technique used in cardiac surgery. A Complete Blood Count called Risk Score (CBC-RS) was calculated from the average of the deviations of the various elements of the CBC and has been previously validated and published. The CBC-RS showed as excellent predictor of death from all causes in large healthy and cardiovascular risk populations. Despite the effect of CPB on the blood cells, there is no acknowledgement from the prior assessment of this score in the surgical setting. The aim of this study was to evaluate the role of CBC-RS in the surgical risk prediction (mortality and morbidity) in patients undergoing cardiac surgery with CPB. For this, it was evaluated a historical cohort of 428 patients undergoing cardiac surgery with CPB. The individual CBC-RS was calculated using the collected blood count of patients preoperatively. Logistic regression and statistical C analyzed the predictive accuracy of this score. The primary endpoint was in-hospital mortality (all-cause) and secondary outcomes included the majors and bleeding complications. In our study, CBC-RS was a predictor of hospital mortality (OR = 1.28 for each score increments, 95% CI = 1123-1458, p <0.001) and secondary outcomes (OR = 1.208, 95% CI = 1.103 to 1.323, p <0.001). The areas under the curve (AUC) was 0.697 (p <0.001) and 0.636 (p <0.001) for both the primary and secondary endpoints, respectively. In multivariate analysis, after adjustment for other risk predictors (EuroSCORE II and CPB time), the CBC-RS remained significant and was the strongest predictor of mortality. Therefore, the CBC-RS proved to be an independent predictor of mortality and surgical complications during hospitalization. It may be a useful tool in risk assessment of patients undergoing cardiac surgery.